Identification of the blast resistance gene Picl(t) from Chaling common wild rice (Oryza rufipogon Griff.). Issue 4 (9th March 2020) - Zheng, Chuanqin; Jiang, Nan; Zhao, Xinhui; Yan, Tianze; Fu, Jun; Li, Yanfeng; Wu, Zhongxiu; Hu, Xiaochun; Bai, Zhenan; Liu, Tiangang; Xiao, Gui; Zhou, Yanbiao; et al.
Abstract: Rice blast, caused by the fungal pathogen Magnaporthe oryzae ( M .  oryzae ), is one of the most destructive and widespread plant diseases in the world. Utilization of resistance genes in rice breeding is considered to be an effective and economical method to control this disease. To identify new sources of blast resistance, a set of 1160 introgression lines (ILs) containing chromosome segments of Chaling common wild rice ( Oryza rufipogon Griff.) in the genetic background of an elite indica rice variety 93‐11 were developed and phenotyped in the blast nursery. Thirty‐three ILs displaying stable blast resistance in three consecutive years were obtained. Among them, one line, IL1043, was subsequently found to be resistant to all of the 28  M. oryzae isolates from different regions through artificial inoculation in greenhouse. By combining bulk segregant analysis coupled with next‐generation sequencing (BSA‐seq) and recessive class analysis (RCA), a major blast resistance gene in IL1043, designated Picl(t), was mapped on rice chromosome 6 flanked by the markers RM527 and Indel6 with an interval of approximately 925 kb, which covers the Pi2/9 locus. These results will facilitate fine mapping and cloning of Picl(t), and the linked markers will further provide a useful tool for rice blast resistance breeding.